e^ pi + 2/pi = pi^3 e^pi + 2pi^2 + c pi^3

e^pi + 2/pi - pi^3 e^pi -2 pi^2 = c pi^3

e^pi / pi^3 + 2 / pi^4 - e^pi - 2/pi = c

(pi e^pi + 2 - pi^4 e^pi - 2pi^3)/pi^4

I messed up on the -2 when it should be +2

Printable View

- Nov 20th 2012, 10:56 PMtjsdndnjsRe: solving initial value problem!
e^ pi + 2/pi = pi^3 e^pi + 2pi^2 + c pi^3

e^pi + 2/pi - pi^3 e^pi -2 pi^2 = c pi^3

e^pi / pi^3 + 2 / pi^4 - e^pi - 2/pi = c

(pi e^pi + 2 - pi^4 e^pi - 2pi^3)/pi^4

I messed up on the -2 when it should be +2 - Nov 20th 2012, 11:01 PMtjsdndnjsRe: solving initial value problem!
e^ pi + 2/pi = pi^3 e^pi + 2pi^2 + c pi^3

e^pi + 2/pi - pi^3 e^pi -2 pi^2 = c pi^3

e^pi / pi^3 + 2 / pi^4 - e^pi - 2/pi = c

(pi e^pi + 2 - pi^4 e^pi - 2pi^3)/pi^4

I messed up on the -2 when it should be +2

Was +2 the difference between mine and yours?

THanks - Nov 20th 2012, 11:10 PMMarkFLRe: solving initial value problem!
Okay, that is equivalent to what I got, which is

$\displaystyle C=\frac{(1-\pi^3)(\pi e^{\pi}+2)}{\pi^4}$